Tinjauan Komunikasi Antar Karyawan Harris Resort Barelang Batam - Edo Ronaldo; Feri Ferdian (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research was motivated by the discovery of problems related to employee communication. The purpose of this research is to determine and describe communication between employees at Harris Resort Barelang Batam. The type of research used is quantitative. The types of data used in this research are primary and secondary data. The population of this research is employees at Harris Resort Barelang Batam. The research sample consisted of 53 with a sampling technique using non-probability sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this research show that employee communication is in the adequate category with an average value of 3.36 from 5 assessment scales, the information acquisition indicator is in the sufficient category with an average value of 3.30, the media quality indicator is in the sufficient category. The average value is 3.40 and the information content indicator is in the sufficient category with an average value of 3.36.